Study of the Impact of the Growth of Settlement Areas Against Decreased Capacity of Shallow Aquifer and Groundwater in Semarang City (2014-2017) - Yudo Prasetyo (Universitas Gadjah Mada, 2019)
The growth of urban areas dominated by residential and industrial land cover will encourage the high use of clean water and land loading (compaction due to building loads). The use of water in people's daily lives and industrial activities still relies on nature, namely in the form of groundwater or aquifers. Continuous water collection, especially in big cities in Indonesia, will have a negative impact on the environment which results in changes in the environment itself. Environmental changes due to the impact of taking water that might occur are land subsidence (LS). For this reason, this study will examine the relationship of the impact of the development of residential areas in the city of Semarang on the decline of shallow aquifer capacity (SAC) and LS.Observation of changes in KAD in this study was observed in the type of shallow aquifer using shallow wells (MAT) data. Whereas for observing land subsidence using the PS InSAR method. For the growth of the residential area of Semarang, it will be focused on the land cover of residential areas in the 2014-2017 period. The overlapping method is used to correlate the effect of changes in KAD and PMT in Semarang City.PS InSAR processing results obtained an average value of average land subsidence per year with a range of 0 ± 3.4 cm to 4.5 ± 3.4 cm and the results of processing obtained the largest land subsidence information found in the District of North Semarang, East Semarang, West Semarang, Pedurungan and Genuk. The change in KAD in the amount of 60% to> a decrease of> 80% occurred in Genuk Sub-District, North Semarang, West Semarang, Pedurungan, Gayamsari. Whereas settlements with population levels based on land use classification maps for settlements are in Genuk, West Semarang, Gayamsari, Pedurungan, Tembalang, and Banyumanik Districts